STRATEGI PANITIA PENYELENGGARA UNTUK MENINGKATKAN PARTISIPASI POLITIK MAHASISWA PADA PEMILU RAYA UPN VETERAN JAKARTA TAHUN 2020 - Abigael Leoni (2022)
This study aims to analyze the strategy of the organizing committee or known as the Implementing Committee (PANPEL) of Pemilu Raya (PEMIRA) UPN Veteran Jakarta) 2020. This study uses a qualitative approach that aims to describe and explore the research. Meanwhile, data collection techniques rely on primary data through interviews and secondary data through observations on various related documents. Based on the results of the study, the strategies carried out by PANPEL PEMIRA UPN Veteran Jakarta 2020 in order to increase political participation of KEMA UPN Veteran Jakarta are by using e-voting method through PEMIRA UPN Veteran Jakarta official website to vote for the election of BEM UPN Veteran Jakarta candidates as well as MPM UPN Veteran Jakarta candidates for the first time. Strategizing a hybrid political socialization campaign, both offline on campus for BEM UPN Veteran Jakarta candidates in accordance with health protocols and holding a live streaming on PEMIRA UPN Veteran Jakarta official YouTube channel and the online campaign for MPM UPN Veterans Jakarta candidates. In disseminating political socialization of PEMIRA UPN Veteran Jakarta in 2020 as well as e-voting tutorials are by using social media in collaboration with Brand Ambassadors, UKM and ORMAWA UPN Veteran Jakarta. Keywords: PANPEL, PEMIRA, e-voting, political participation, political socialization, social media, strategy theory